Quality of grip waxing and the force production in classical skiing - Linnamo, V.; Piirainen, J.; Vähäsöyrinki, P.; Komi, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Horizontal force during the kick phase in classical skiing is depending on the GRIP waxing quality of the ski (Komi 1987). The effect of waxing is likely to be even more substantial in uphill skiing with shorter gliding phase. The purpose of the present study was to examine the effects of waxing on the force production and skiing speed in steep uphill classical skiing. In addition it was examined if the waxing properties affect the force production and gliding properties when measured using a novel ski tester. Methods 7 experienced male skiers (age 21.7 + 5.1 years) skied 11 °; uphill with maximal speed with three different waxing conditions (slippery, medium grip and good grip). Vertical and horizontal forces of both skis and poles were measured with a 12m long force plate system. After the subject had skied over the force plates the ski was attached to a ski tester (Linnamo et al. 2008). The pressure against the force plates was adjusted to be 60% of the body weight (BW) for each subject. In addition, gliding phase was measured with 150% BW. All the measurements took place in indoor Ski Tunnel in Vuokatti Sports Institute. Results: No major differences were observed in maximal pole forces or in maximal vertical ski forces while the maximal horizontal force during kick phase increased significantly (P<.01) as a result of better grip (slippery 154 + 27 N, medium grip 168 + 53 N, good grip 279 + 66 N). This led to a significant (P<.01) increase in skiing speed (slippery 3.5 + 0.4 m/s, medium grip 4.1 + 0.3 m/s, good grip 4.5 + m/s). Ski tester with 60% BW showed no significant differences in maximal vertical force but maximal horizontal force was significantly higher (P<.05) in good grip condition than in slippery. Horizontal force in the gliding phase was similar in 60% BW between different waxing conditions but with 150% BW it increased significantly (P<.01) from slippery to good grip. Discussion: This study showed that in a steep uphill (11°) the horizontal ski forces and skiing speed are remarkably improved with better grip wax conditions. While the skiing speed decreased with slippery waxing the pole forces remained similar in all conditions. This suggests that the horizontal ski force loss cannot be compensated with pole forces when skiing with maximal speed. As expected the maximal skiing speed in the present study (4.5 m/s) was lower than earlier observed (5.6 m/s) in 2.5 °; uphill skiing (Vähäsöyrinki et al 2008). Due to steep uphill the gliding phase was almost non existent thus slowing down the speed. On the other hand even better grip did not affect the gliding properties as was the case with 150% BW in ski simulator. During kicking phase the ski simulator was able to differentiate the horizontal forces between waxing conditions even with only 60% BW.